Sovereign default risk and commodity prices - Lazzaro, João Guilherme Santos (2017)
Country risk is known to be an important driver of emerging economies business cycles. Existing studies of macroeconomics effects of commodities prices on emerging economies' country risk assume an exogenous negative relation between these two variables. This work presents a model to explain endogenously this relation built upon the sovereign debt literature deriving from Arellano (2008). Our framework is then used to assess quantitatively the importance of the country risk effect of commodity prices on output volatility. We find that although this effect is negligible for economies with a high share of commodities on GDP but low indebtedness, the effect is important in indebted economies with a lower share of commodities in GDP.